"Islam Nusantara" dan Globalisasi - Fachry Ali (Indonesian Journal of Islamic History and Culture, 2020)
Studies on Islam Nusantara have been present since the discourse started. In this study, "Islam Nusantara" is described as a religious expression "without theological pressure." The experience of Aris and Harjono, two intellectuals of global products who find a path of religious mystery without intellectual rebellion is a picture of the journey in which the local is able to integrate with the global. There is a spirit of reason and a post-reason that cause global products to unite with religious mysteries. Islam Nusantara appears with a social style without theological pressure. As stated by Durkheim, religion is a collective conscience. However, the next question as asked by Abdul Aziz, can religious diversity be an integrative force? yes, as long as religion resists its lust of identity and submits to the desire for harmony. Globalization is not a challenge, but a support, as long as "Islam Nusantara" is a social expression of religion and rejects hierarchy in religious relations. "Islam Nusantara" will not act as a wall that will isolate itself from extra-Nusantara influences. Like Aris's "new" spiritual experience, every wall that isolates itself will only make "Islam Nusantara" lose its true character.